ENVIRONMENTAL CRIME ACCOUNTABILITY VIEWED FROM THE PERSPECTIVE OF CRIMINAL LAW IN INDONESIA - Orlando Beremanda, Lukas Permadi (Communale Journal, 2025)
The environment is the unity of space with all objects and living things in it including humans and their behavior that can affect the continuity of life between humans and the surrounding environment. At this time environmental damage, especially in Indonesia, is increasingly concerned, if left unchecked, it will gradually threaten human life itself. Environmental damage in addition to being caused by natural conditions is also generally caused by damage caused by human activities that exploit nature excessively such as forest destruction, illegal tree felling, pollution of water, air, soil and so on. This study discusses criminal responsibility for the environment from the perspective of criminal law in Indonesia and the vagueness of norms regarding the regulation of B3 waste dumping. This research uses a type of normative research which is then described descriptively analytically with argumentative techniques. Indonesia's positive law regulates the environment in Law Number 32 of 2009 concerning Environmental Protection and Management, it is hoped that future criminal law policies in overcoming environmental crimes from the perspective of criminal law can be known from various aspects such as criminalization policies, criminal responsibility and punishment.